A nosedive into Bertapak Buana - Sanusi, Aliyah Nur Zafirah; Abdul Halim, Khairunnisa; Muhammad Taufik, Muhammad Muzzammil (Kulliyyah of Architecture & Environmental Design, International Islamic University Malaysia, 2020)
The Kulliyyah of Architecture and Environmental Design (KAED), IIUM was given a stretch of land within the campus to develop the Malay Enclave Project. The Malay Enclave Project was initiated in 2017 through the preservation and relocation of the 111 years old Rumah Kutai from the state of Perak as a move towards preserving the Malay heritage and architecture as part of the UNESCO Sustainable Development Goal (SDG) initiative. “Reminiscing the Tradition” is the overall project concept to recall the continuity of Malay culture-their customs and institutions as well as their social attitudes. Under the Malay Enclave Project, a multidisciplinary KAED student group from the three disciplines-Architecture, Interior Design and Quantity Surveyor; were given the task to design IIUM Cultural and Natural Heritage Living Centre. The site was divided into four different plots. Each team were required to produce a strong concept and work together to create a masterplan of IIUM Cultural and Natural Heritage Living Centre. The team is also required to design five gazebos in the masterplan that reflect the Bugis culture. Bugis is one of the Malay Nusantara culture found in Gombak. The Gazebo is to be designed to budget.